Phase transformations in an ascending adiabatic mixed‐phase cloud volume. Issue 8 (16th April 2015) - Pinsky, M.; Khain, A.; Korolev, A.
Abstract Regimes of liquid‐ice coexistence that may form in an adiabatic parcel ascending at constant velocity at freezing temperatures are investigated. Four zones with different microphysical structures succeeding one another along the vertical direction have been established. On the basis of a novel balance equation, analytical expressions are derived to determine the conditions specific for each of these zones. In particular, the necessary and sufficient conditions for formation of liquid water phase within an ascending parcel containing only ice particles are determined. The results are compared to findings reported in earlier studies. The role of the Wegener‐Bergeron‐Findeisen mechanism in the phase transformation is analyzed. The dependence of the phase relaxation time on height in the four zones is investigated on the basis of a novel analytical expression. The results obtained in the study can be instrumental for analysis and interpretation of observed mixed‐phase clouds.